Openly straight - Konigsberg, Bill (Arthur A. Levine Books, 2013)
Tired of being known as "the gay kid", Rafe Goldberg decides to assume a new persona when he comes east and enters an elite Massachusetts prep school--but trying to deny his identity has both complications and unexpected consequences.